Restorative treatment of victims with multiple gunshot fractures of long bones - Buryanov, Oleksandr; Kazmirchuk, Anatoliy; Yarmolyuk, Yuriy; Vakulych, Myroslav; Drychyk, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Due to the large number of victims of the armed conflict in the east of Ukraine with multiple long-bones gunshot fractures, there was a need for comprehensive and step-by-step restorative treatment at all levels of medical evacuation, especially at III and IV. Objective: to develop a step-by-step system for the rehabilitation of victims with multiple long-bone fractures and to prove its effectiveness in preventing the most common complications. Methods: 380 patients were divided into three groups: the developed system and individual programs of medical rehabilitation were used in the main (119 people), in I (118) — modern conventional methods of treatment, in II (143 wounded in Afghanistan) — methods, used in the 80th of the twentieth century, with effective rehabilitation. To assess the results of treatment, the Luboszyce-Mattisa-Schwarzberg scale was chosen in the modification of Shevtsov. Results: a rehabilitative treatment system was developed, including a reasoned replacement of the fixation method (biochemical and clinical blood tests, evaluation of the limb state), an algorithm for surgical treatment using modern medical techniques (VAC- therapy, ultrasound cavitation, Vivostat® PRF) and IDEP. The best long-term results (1.2–1.5 years) were obtained in patients of the main group compared with I and II. The risk of contamination of the operating wound in the patients of the main group decreased by 5.8 %, the occurrence of osteomyelitis by 4.2 %, the incidence of neurologic deficits by 2.4 %, vascular disorders by 7.3 %, the development of false joints by 2.8 %, contractures — by 11.3 %. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> the proposed system of restorative treatment of multiple long-bone fractures is effective in preventing the most common complications.